Polymorphisms in stearoyl coa desaturase and sterol regulatory element binding protein interact with N‐3 polyunsaturated fatty acid intake to modify associations with anthropometric variables and metabolic phenotypes in Yup'ik people. Issue 12 (15th September 2016) - Lemas, Dominick J.; Klimentidis, Yann C.; Aslibekyan, Stella; Wiener, Howard W.; O'Brien, Diane M.; Hopkins, Scarlett E.; Stanhope, Kimber L.; Havel, Peter J.; Allison, David B.; Fernandez, Jose R.; Tiwari, Hemant K.; Boyer, Bert B.
Abstract : The present study investigates how consumption of n‐3 polyunsaturated fatty acid (n‐3 PUFA) modifies associations between stearoyl CoA desaturase (SCD), insulin‐sensitive glucose transporter (SLC2A4), and sterol regulatory element binding protein (SREBF1) polymorphisms and anthropometric variables and metabolic phenotypes in Yup'ik people. The results suggest that an individual's genotype may interact with dietary n‐3 PUFAs in ways that are associated with protection from obesity‐related diseases in Yup'ik people. Abstract : Scope: n‐3 polyunsaturated fatty acid (n‐3 PUFA) intake is associated with protection from obesity; however, the mechanisms of protection remain poorly characterized. The stearoyl CoA desaturase ( SCD ), insulin‐sensitive glucose transporter ( SLC2A4 ), and sterol regulatory element binding protein ( SREBF1) genes are transcriptionally regulated by n‐3 PUFA intake and harbor polymorphisms associated with obesity. The present study investigated how consumption of n‐3 PUFA modifies associations between SCD, SLC2A4, and SREBF1 polymorphisms and anthropometric variables and metabolic phenotypes. Materials and methods: Anthropometric variables and metabolic phenotypes were measured in a cross‐sectional sample of Yup'ik individuals ( n = 1135) and 33 polymorphisms were tested for main effects and interactions using linear models that account for familial correlations. n‐3 PUFA intake was estimated using red blood cell nitrogen stable isotope ratios. SCD polymorphisms were associated with ApoA1 concentration and n‐3 PUFA interactions with SCD polymorphisms were associated with reduced fasting cholesterol levels and waist‐to‐hip ratio. SLC2A4 polymorphisms were associated with hip circumference, high‐density lipoprotein and ApoA1 concentrations. SREBF1 polymorphisms were associated with low‐density lipoprotein and HOMA‐IR and n‐3 PUFA interactions were associated with reduced fasting insulin and HOMA‐IR levels. Conclusion: The results suggest that an individual's genotype may interact with dietary n‐3 PUFAs in ways that are associated with protection from obesity‐related diseases in Yup'ik people.